THE IDENTITY CONFLICT OF THE SYMBOLIC DOMINATION DISCOURSE IN THE SHORT STORIES OF MODERN CIVILIZATION - Eka Ugi Sutikno (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
In this modern-day, many women have a suitable carrier; however, they often have seemed like a weak person. One of their weaknesses that often shown is the unableness of how to make any decision. These things often happen in real life and stated in the literature, especially in short stories. The Anatomy by Padrika Tarrant and the Otobiografi Gloria by AS Laksana are literary works that are containing the identity conflict of the symbolic domination discourse. The research purpose is to analyze the identity conflict of the symbolic domination discourse in these short stories. The method of this research is using the qualitative descriptive because the subjects are short stories. The result of this research has shown the two main characters of these short stories, which dominated on symbolic and they live in the marginal as the women who have an identity. The conclusion of this research has drawn that women in this modern era still dominated on symbolic and as a weak person.